Serum calcification propensity in type 1 diabetes associates with mineral stress. (December 2019) - van Dijk, Peter R.; Hop, Hilde; Waanders, Femke; Mulder, Udo J.; Pasch, Andreas; Hillebrands, Jan-Luuk; van Goor, Harry; Bilo, Henk J.G.
Highlights: An association of T50 time with serum parameters of increased mineral stress is present in T1DM. The T50 test measures calcification propensity in serum. T50 time was not associated with macrovascular complications in this small cohort. Abstract: Aims: Increased vascular calcification could be an underlying mechanism of cardiovascular complications in type 1 diabetes mellitus (T1DM). Calcification propensity can be monitored by the maturation time of calciprotein particles in serum (T50 test). A high calcification propensity (i.e. low T50 -value) is an independent determinant of mortality in various populations. Aim was to investigate T50 levels with indices of calcium metabolism and disease status in T1DM patients. Methods: As part of a prospective cohort study, T1DM patients were examined annually. At baseline T50 was determined in 216 (77%) patients (57% male) with a mean age of 45 (12) years, diabetes duration 22 [15.8, 30.4] years and HbA1c of 60 (12) mmol/mol (7.6 (1.0) %). Baseline data were collected in 2002 and follow-up data were collected in 2018. Results: The T50 time was normally distributed with a mean of 339 (60) minutes. Patients in the highest tertile of T50 (range 369–466) were older, had lower phosphate and PTH and higher magnesium and vitamin D concentrations as compared to the middle (range 317–368) and lowest (range 129–316) tertiles, while eGFR was comparable between groups. During follow-up of 15 years, 43 patients developed a macrovascular complication and 26 patients died. In regression analysis, T50 was not a prognostic factor for the development of complications or mortality. Conclusions: The T50 time was associated with indices of increased mineral stress, but not with the development of long-term macrovascular complications.